Guidelines for Authors -Journal of Food Technology, Siam University - Thaiphanit, Somruedee (Journal of Food Technology, Siam University, 2019)
Journal of Food Technology, Siam University covers the research of food science and technology such as food chemistry, food processing, food engineering, food microbiology and food quality assurance including nutrition, postharvest technology, packing technology and product development. Journal of Food Technology, Siam University is a double-blind peer reviewed journal which is published 2 issues per year in January and July. Articles submitted to the journal must be a work that has never been published before and not in the process of publishing in any other journals. The articles published in the journal must be peer-reviewed by a minimum of two expert reviewers per article and operated by a double-blind assessment. Two types of peer-reviewed papers will be published: 1) Research articles which are written according to article structure stating the problem(s), objectives of the work, research methodology, discussion and conclusions which contributes new knowledge to its field or further applications. 2) Review articles which are written to present new aspects on the topic of current interest that include major findings and compile literatures form several sources or address in-depth interpretive and concise reviews on the academic aspects.